Inventory of Pest and Disease in Mango Plants (Mangifera indica) - Tanzil, Ahmad Ilham; Sucipto, Irwanto; Muhlison, Wildan (Talenta Publisher, 2022)
Mango is a local fruit that is widely grown in Indonesia. Mango has several benefits for human life, including as a source of vitamins and industrial raw materials. This study aims to obtain pathogenic fungi that have the ability to cause disease in mango plants. This research was conducted in mango orchards in the provinces of South Sumatera, West Kalimantan, East Java, and Bali. Pathogenic fungi were observed from stems, leaves, and fruit. All symptoms of physiological and morphological deviations were observed to identify the cause. Then the identification procedure uses a supporting literature library. Pathogenic fungi were found, namely Xanthomonas citri pv. mangiferaeindicae, Ganoderma lucidum, Elsinoe mangiferae, Colletotrichum gloeosporioides, Ganoderma applantum, Paratetranychus yothersi, and Bemisia tabaci.